2009
DOI: 10.1155/2009/760793
|View full text |Cite
|
Sign up to set email alerts
|

Adrenaline Injection Plus Argon Plasma Coagulation versus Adrenaline Injection Plus Hemoclips for Treating High-Risk Bleeding Peptic Ulcers: A Prospective, Randomized Trial

Abstract: BACKGROUND/OBJECTIVE: Several combination endoscopic therapies are currently in use. The present study aimed to compare argon plasma coagulation (APC) + adrenaline injection (AI) with hemoclips + AI for the treatment of high-risk bleeding peptic ulcers.METHODS: In a prospective randomized trial, 172 patients with major stigmata of peptic ulcer bleeding were randomly assigned to receive APC + AI (n=89) or hemoclips + AI (n=83). In the event of rebleeding, the initial modality was used again. Patients in whom tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 32 publications
0
7
0
2
Order By: Relevance
“…Three RCTs of comparable size (n = 151 to n = 185) have evaluated the effectiveness of APC plus epinephrine versus other modalities (heater probe, clip, hemostatic forceps) plus epinephrine for treatment of peptic ulcer bleeding 57, 60, 61. In all 3 trials, there were no significant differences between the 2 groups in terms of initial hemostasis (>95% in all treatment arms), recurrent bleeding, or other relevant clinical outcomes.…”
Section: Outcomes Datamentioning
confidence: 99%
“…Three RCTs of comparable size (n = 151 to n = 185) have evaluated the effectiveness of APC plus epinephrine versus other modalities (heater probe, clip, hemostatic forceps) plus epinephrine for treatment of peptic ulcer bleeding 57, 60, 61. In all 3 trials, there were no significant differences between the 2 groups in terms of initial hemostasis (>95% in all treatment arms), recurrent bleeding, or other relevant clinical outcomes.…”
Section: Outcomes Datamentioning
confidence: 99%
“…The majority of UNVGIB could be managed by conventional endoscopic interventions. However, some studies have shown that conventional therapies such as epinephrine injections and hemoclips or coagulation could not achieve successful hemostasis in 4 to 20% of UNVGIB cases, and even caused severe complications [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have shown that conventional therapies such as epinephrine injections and hemoclips or coagulation could not achieve successful hemostasis in 4 to 20% of UNVGIB cases, and even caused severe complications. [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%